Incidence of alveolar capillary dysplasia with misalignment of pulmonary veins in infants with unexplained severe pulmonary hypertension: The roles of clinical, pathological, and genetic testing. (April 2021) - Onda, Tetsuo; Akimoto, Takuma; Hayasaka, Itaru; Ikeda, Masahiko; Furuse, Yuta; Ando, Akiko; Nakamura, Yuichi; Honjo, Ryota; Manabe, Atsushi; Furuta, Itsuko; Cho, Kazutoshi
Abstract: Background: Alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV) is a rare and fatal disorder that occurs in the developing fetal lungs; at birth, infants exhibit an oxygenation disorder accompanied by severe pulmonary hypertension (PH) and have a very short life span. ACDMPV is definitively diagnosed by pathological findings, and infants born with unexplained severe PH may not be properly diagnosed without a biopsy or autopsy. Methods: Japanese infants with unexplained severe PH were enrolled in this study. Genetic analyses were performed on DNA extracted from peripheral blood leukocytes. Sanger sequencing or next-generation sequencing was performed by coding exons and introns for FOXF1 in all samples. For individuals without pathogenic exonic variants, multiplex ligation-dependent probe amplification was performed to identify copy number variations (CNVs) in exons, introns, and in the upstream region of FOXF1 . Results: This study included 30 infants who were diagnosed over the course of nine years. Four individuals had the pathogenic variations on the exon 1 of FOXF1, including two frameshift and two missense variations. Pathogenic CNVs were found in another five individuals. Conclusion: In the pathologically proven ACDMPV patients, the ratios of cases with exonic variations, CNVs, and no genetic findings were reported as 45%, 45% and 10%, respectively. We estimate that about 30% (10 (9 + 1) out of 30) of individuals with unexplained severe PH had ACDMPV. Highlights: This is the first report estimating the incidence of ACDMPV in unexplained severe infantile pulmonary hypertension. ACDMPV cases frequently have symptoms at birth, but the disease is not well identified. Genetic analysis could be useful for diagnosing ACDMPV without pathological examination. ACDMPV cases genetically diagnosed without pathological examination often have extrapulmonary anomalies.